Desain Pengembangan Kurikulum Integratif - Zainiyati, Husniyatus Salamah (NADWA, 2014)
Implementation of an integrated curriculum in UIN Maliki seeks to provide basic competencies of Islamic sciences as a characteristic of UIN, as well as the foun-dation for the development of fields of study are developed on existing majors. Study program tali>m al-afka>r al-Isla>miyyah and tali>m al-Qurâa>n not only dis-cuss the matter as Fiqh, Sufism, Aqeedah, but the study needs to be developed by taking the material Quran and Hadith relating to the development of science and technology. Basic Islamic knowledge can be used for students or faculty development studies field according to the respective department. The program not only as a prerequisite studies program at UIN Islamic subjects, but can be used to support other subjects. Mahad tradition intended to form the character of students and develop Islamic culture on campus.